PENERAPAN SISTEM AKUNTANSI BERBASIS ANDROID GUNA PENINGKATAN KUALITAS PENYUSUNAN LAPORAN KEUANGAN UMKM BUDIDAYA IKAN HIAS DESA GEMPOLAN PAKEL TULUNGAGUNG - Lelyana Wahyuningtyas; Dyah Pravitasari (Jurnal Akuntansi dan Pajak, 2022)
The development of information technology has a very rapid impact on the Accounting System. As in recording financial statements, which are increasingly made easier through financial bookkeeping applications on Android smartphones. The benefits of implementing an Accounting System in business will make it easier for MSME actors to evaluate performance, and find out financial position. The purpose of this study is to understand the implementation of an android-based accounting information system with the BukuKas application to improve the quality of the economic activities of SMEs located in Gempolan Village, Pakel District, Tulungagung Regency and work in the field of ornamental fish cultivation which is located in terms of making financial reports. This research activity uses a method in the form of a qualitative method, while the data used during the research is in the form of raw or primary data obtained face-to-face by interviewing business actors. In carrying out their business, these ornamental fish cultivation MSME actors only remember a transaction without being disabled and care about their financial condition. With the BukuKas application, it can help prepare financial reports for free, effectively and efficiently so that it looks more professional in its business operations.